Two-dimensional mapping of micro-hardness increase on surface treated steel determined by photothermal deflection microscopy - Crossa Archiopoli, Ulises (2011)
An optical noncontact technique is presented that provides a two-dimensional map of the hardness of treated steel at the micrometer level. The photodeflection technique for determining the thermal diffusivity is shown to be a useful and rapid way to determine the hardness increase profile in two dimensions with only minor preparation of the sample (flat polish). This is possible due to the strong correlation found for this type of material between the inverse of the diffusivity and the hardness increment after treatment. The diffusivity retrieval is performed by a single measurement of the phase delay between the pump beam and the photodeflection signal thus allowing a rapid scanning of the surface. The surface scans of the hardness performed with this technique showed that anomalous regions can be identified that direct optical or scanning electron microscopy observation do not reveal.